CORRELATION BETWEEN KNOWLEDGE AND DECISIONS EXACTNESS OF THE FACE WHITENING COSMETIC PRODUCTS SELECTION IN TEENAGE GIRLS OF SUMBERPINANG VILLAGE JEMBER - Amaliyah Nurul Hidayah; Lilis Wulandari; Dewi Rashati; Dewi Riskha (AKADEMI FARMASI JEMBER, 2022)
Facial whitening cosmetics are preparations or combinations of ingredients that used on the outside of the body that serves to brighten or change skin color become white, clean and shining. The purpose of this study was to determine the correlation between knowledge and decisions exactness about facial whitening cosmetic products in teenage girls of Sumberpinang Village, Jember, (period of June 2022). The type of research conducted was descriptive research. the survey design was cross sectional. Sampling technique by using consecutive sampling which done by door to door. The total sample in this study was 70 respondents according to the criteria inclussion that has been determined. Bivariate analysis results with Kendall's correlation test obtained p value = 0,001 (p0,05),which means there was correlation between knowledge and decision on the selection of facial whitening cosmetic products in teenage girl. The correlation coefficient obtained was 0,386 which indicates weak correlation. It can be concluded that there was weak correlation between knowledge and decisions exactness about facial whitening cosmetic products in teenage girls of Sumberpinang Village, Jember (period of June 2022).Keyword : knowledge level, teenage girls, decisions exactness, face whitening cosmetic